Human surfactant protein D facilitates SARS-CoV-2 pseudotype binding and entry in DC-SIGN expressing cells, and downregulates spike protein induced inflammation - Beirag, Nazar; Kumar, Chandan; Madan, Taruna; Shamji, Mohamed H.; Bulla, Roberta; Mitchell, Daniel; Murugaiah, Valarmathy; Neto, Martin Mayora; Temperton, Nigel; Idicula-Thomas, Susan; Varghese, Praveen M.; Kishore, Uday (Frontiers in Immunology, 2022)
Lung surfactant protein D (SP-D) and Dendritic cell-specific intercellular adhesion molecules-3 grabbing non-integrin (DC-SIGN) are pathogen recognising C-type lectin receptors. SP-D has a crucial immune function in detecting and clearing pulmonary pathogens; DC-SIGN is involved in facilitating dendritic cell interaction as an antigen-presenting cell with naïve T cells to mount an anti-viral immune response. SP-D and DC-SIGN have been shown to interact with various viruses, including SARS-CoV-2, an enveloped RNA virus that causes COVID-19. A recombinant fragment of human SP-D (rfhSP-D) comprising of α-helical neck region, carbohydrate recognition domain, and eight N-terminal Gly-X-Y repeats has been shown to bind SARS-CoV-2 Spike protein and inhibit SARS-CoV-2 replication by preventing viral entry in Vero cells and HEK293T cells expressing ACE2. DC-SIGN has also been shown to act as a cell surface receptor for SARS-CoV-2 independent of ACE2. Since rfhSP-D is known to interact with SARS-CoV-2 Spike protein and DC-SIGN, this study was aimed at investigating the potential of rfhSP-D in modulating SARS-CoV-2 infection. Coincubation of rfhSP-D with Spike protein improved the Spike Protein: DC-SIGN interaction. Molecular dynamic studies revealed that rfhSP-D stabilised the interaction between DC-SIGN and Spike protein. Cell binding analysis with DC-SIGN expressing HEK 293T and THP- 1 cells and rfhSP-D treated SARS-CoV-2 Spike pseudotypes confirmed the increased binding. Furthermore, infection assays using the pseudotypes revealed their increased uptake by DC-SIGN expressing cells. The immunomodulatory effect of rfhSP-D on the DC-SIGN: Spike protein interaction on DC-SIGN expressing epithelial and macrophage-like cell lines was also assessed by measuring the mRNA expression of cytokines and chemokines. The RT-qPCR analysis showed that rfhSP-D treatment downregulated the mRNA expression levels of pro-inflammatory cytokines and chemokines such as TNF-α, IFN-α, IL-1β, IL- 6, IL-8, and RANTES (as well as NF-κB) in DC-SIGN expressing cells challenged by Spike protein. Furthermore, rfhSP-D treatment was found to downregulate the mRNA levels of MHC class II in DC expressing THP-1 when compared to the untreated controls. We conclude that rfhSP-D helps stabilise the interaction of SARS- CoV-2 Spike protein and DC-SIGN and increases viral uptake by macrophages via DC-SIGN, suggesting an additional role for rfhSP-D in SARS-CoV-2 infection.